The Effectiveness of Physics E-Modules Based on Creative Problem-Solving Learning Model Integrated with 21st-Century Skills - Widya, Widya; Andriani, Riza; Sudirman, Sudirman; Hidayat, Amam Taufiq; Elisyah, Nur (Universitas Islam Negeri Raden Intan Lampung, 2023)
The availability of teaching materials that contain 21st-century skills still needs to be improved. This research aims to look at the effectiveness of the 21st-century integrated CPS-based e-module that has been developed. This study is part of Research and Development research, using the Reeve Model with stages of analysis, design, and evaluation. Measurement of effectiveness is carried out at the evaluation stage. Effectiveness is measured by giving a pretest and posttest to students. The sampling technique used is a purposive sample. Effectiveness is measured by giving a pretest and posttest to students. There was an increase in student mastery of 21st-century skills from 78.32 to 84. Then, based on hypothesis testing, information was obtained that there were differences in student mastery of 21st-century skills before and after using the e-module (Sig (2-tailed)<0.05). It indicates the effect of using e-modules based on the CPS model integrated with 21st-century skills to improve student mastery of 21st-century skills and mastery of 21st-century skills.